Arbitration: Understanding It in Theory and Indonesian Practice - Maskun, Maskun; Achmad, Achmad; Naswar, Naswar; Bakti, Fauziah P.; Amaliyah, Amaliyah (Faculty of Law, Hasanuddin University, 2019)
Cross-border transactions have always attracted legal risks. Cross-border legal issues are emerging as a separate area of commercial risk that needs to be more precisely identified and better managed. Many cases of injury to multinational companies which would formerly have been pursued as a diplomatic claim by the nation state of the company are now resolved by arbitration between the company and the respondent state. Arbitration is one of dispute settlement bodies to resolve some issues particular trade, business, investment, and financial issues. Those issues are shaping the range and significance of the cross-border legal issue. Those issues also become a crucial issue to be dealt with the arbitral institution. The reason why the parties of contract choose arbitration is because of the place of arbitration, neutrality, confidentiality, cost and speed, recognition and enforcement of arbitral awards, refusing of arbitral awards, a model of arbitration, and arbitration institution. Those reasons are assumed also to be enacted in Indonesian arbitration practice and in the Islamic law.